Implementation of a PID Type Sliding-Mode Controller Design Based on Fractional Order Calculus for Industrial Process System - Ayten, Kagan Koray; Dumlu, Ahmet (Elektronika ir Elektrotechnika, 2021)
This paper is devoted to designing a fractional order Proportional Integral Derivative (PID) type sliding mode control method (FO-PIDSMC) for a non-linear liquid level coupled tank process system. By considering the individual advantages of the FO calculus and PID type SMC method, this proposed FO-PIDSMC technique is designed to integrate the FO calculus method with PID type SMC scheme to obtain an accurate and robust liquid level tracking in terms of the predefined reference trajectory. The real-time experimental results of the proposed controller suggest a dramatic improvement over the traditional process system controller methods in both trajectory tracking and required control action.